Shot at Dawn: Late photography and the anti-war memorial. Issue 2 (3rd April 2019) - McCulloch, Lynsey; Tovey, Rob
Abstract : The military executions of World War One are the subject of Chloe Dewe Mathews's 2014 photographic series Shot at Dawn. These events—in which hundreds of soldiers were court-martialled and executed for cowardice and desertion—remain controversial, without consensus or established collective narrative. This article charts historic negotiations with the subject but also considers more recent efforts to integrate these proceedings within memorial practice. World War One remembrance activities, whilst diverse, have often emphasised sacrifice, heroism and community. Correspondingly, participation and engagement were core values in the major British World War One centenary arts project, titled 14-18 NOW, from which Shot at Dawn was commissioned. Chloe Dewe Mathews's contribution to the programme, however, presents a photographic aesthetic of resistance to the principles of inclusivity and remembrance elsewhere embraced by the project. As such, the work challenges the consensual politics of commemoration and—through the practices of late photography, land art and performance pilgrimage—substitutes trauma and forgetfulness for reconciliation and memory.